Tindak Pidana Penganiayaan terhadap Hewan Perspektif Fikih Jinayah - Qamariah, Zannuba; Halimatusyadiah, Halimatusyadiah; Natun, Dwi Us; Ahmad, Sabarudin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Animals are often humans' pets, which are useful for playing, making friends, or acting as guardians. but some people actually use animals, exploit, abuse, and even kill them for certain interests. Currently, the problem of mistreatment of animals is increasingly apprehensive. Through information in various media, cases of mistreatment of animals can be identified. Islam as the majority religion in Indonesia teaches to be a mercy to the universe, including taking care of animals on earth. However, Indonesia is the country with the largest number of downloaders of animal abuse content in the world. Therefore, the purpose of this study is to analyze these problems in the perspective of jurisprudence. The research method used is normative legal research with a statutory approach and analysis of Islamic legal theories. The results of this study indicate that the crime of mistreatment of animals in Indonesia is regulated in the Criminal Code (KUHP) Article 302 and Article 540, as well as Law Number 18 of 2009 as amended by Law Number 41 of 2014 concerning Animal Husbandry and Health. Animal abuse in jinayah fiqh is included in the jarimah ta'zir, in which the level and punishment is determined by the government (ulil amri).